Analysis of Family Preparedness in Flood Disaster - Setianingsih Setianingsih; Lestari Eko Darwati; Anggita Anggita Setyowati (Global Health Science Group, 2020)
The family is part of the community, preparedness of disaster must be owned by the family because has an important role namely planning for family rescue in the event of a disaster emergency in determining whether or not ready impending disasters. Flood disasters often cause losses such as home, environment, property, and life. The purpose of this research is to analyze of family preparedness in flood disaster in Kendal Regency. The design of this research is descriptive survey approach. The sample in this study amounted to 157 family heads with proportional random sampling technique. Data collecting with form of a questionnaire with the validity test was in the range 0,468-0,786 and reliability test was 0,875. The analysis used an univariate. The results showed that the characteristics of family heads based on gender were dominated by male as many as 155 (98.7%), the average age was 40 years old with the youngest age 23 years and the oldest age was 72 years, the majority of high school education was 114 (72.6%) and labor dominated by 62 heads of family (39.5%). Family preparedness to flood disaster, majority was high categories were 103 heads of families (65.6%). The result of this study prove that people in Kendal regency are ready to face flood disaster.